Interculturalismo en Europa: el referente de las segundas generaciones españolas en Francia - Santos Rego, Miguel Anxo (2000)
With this article, our intention is to contribute towards a better knowledge and analysis of the educational, social and cul-tural problems of descendants of Spanish emigrants in France -at such a crucial time as the present- in which the European Union is growing fast. In the article we examine the evolution of interculturalism and establish a number of connections with the civil society. We emphasize the presence of our (Galician) emigration in the French society and deri-ve possible means of socio-educational intervention, highlighting the value and use of the proposals, which particularly cen-tre their attention on these second generation emigrants.